2014
DOI: 10.1091/mbc.e14-06-1121
|View full text |Cite
|
Sign up to set email alerts
|

TACC3 is a microtubule plus end–tracking protein that promotes axon elongation and also regulates microtubule plus end dynamics in multiple embryonic cell types

Abstract: TACC3 is a microtubule plus end–tracking protein in vertebrates. TACC3 localizes to the extreme microtubule plus end, where it interacts with XMAP215 to regulate microtubule polymerization. TACC3 is also required to promote normal axon outgrowth, likely through its regulation of microtubule dynamics within the growth cone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
99
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 57 publications
(114 citation statements)
references
References 49 publications
14
99
1
Order By: Relevance
“…3C). These results were similar to previous MT dynamics effects by TACC3 OE [Nwagbara et al, 2014] (and also shown in Figs. 3A–3C), suggesting that TACC1 may modulate MT plus‐end dynamics through a mechanism related to that of TACC3.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3C). These results were similar to previous MT dynamics effects by TACC3 OE [Nwagbara et al, 2014] (and also shown in Figs. 3A–3C), suggesting that TACC1 may modulate MT plus‐end dynamics through a mechanism related to that of TACC3.…”
Section: Resultssupporting
confidence: 93%
“…1O). While these are imprecise measurements based on experimental limitations, it is notable that they are consistent with the previous measurement of 0.5 μm between mKate2‐EB1 and GFP‐TACC3 [Nwagbara et al, 2014]. Additionally, we observed that the GFP‐TACC1 plus‐end accumulations were considerably lengthened upon overexpression of mKate2‐TACC3 (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations